Death and dying in the Neolithic Near East - Croucher, Karina ca. 20./21. Jh. (Oxford Oxford University Press, 2012)
The Neolithic of the Near East is a period of human development which saw fundamental changes in the nature of human society. It is traditionally studied for its development of domestication, agriculture, and growing social complexity. This book takes a new approach, focusing on the human body and investigating mortuary practices - the treatment and burial of the dead - to discover what these can reveal about the people of the Neolithic Near East
Includes bibliographical references and index
Keywords: Funeral rites and ceremonies, Ancient -- Middle East; Neolithic period -- Middle East; Funeral rites and ceremonies, Ancient ; Middle East; Neolithic period ; Middle East